'Churchill abandoned the fighting Scots': The Mythology and Reality of the Surrender of the 51st Highland Division at St Valery-en-Caux, 12 June 1940. Issue 1 (February 2023) - Barclay, Gordon J.; Brown, Adam
Abstract : The 51st (Highland) Division surrendered to the Germans on 12 June 1940. The force lost at St Valery was made up not only of Scots, but also English, Welsh, French and French Colonial troops. But in recent decades the division's loss has been recast as a story of solely Scottish loss, deployed in narratives of grievance and victimhood. We contrast the mythology with the historical reality, in the context of the distribution of 'fake history' in the service of nationalist politics ( English 2021 ). This paper considers three aspects of the events of 1940: 1. The creation, development and use of the mythology. 2. The nature of the 51st Highland Division – how 'Highland', how 'Scottish' was the force lost at St Valery? 3. The actual events of May-June 1940. We do this by drawing together existing and new scholarship, including more from French perspectives than is common, to summarise knowledge in an accessible form for a wider audience.